PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS LINGKUNGAN HIDUP KOTA TIDORE KEPULAUAN - Adnan Rajak; Muhammad Thahrim (Jurnal Manajemen Sinergi, 2019)
influence of motivation on employee performance : (2) Knowing and analyzing the influence of work discipline on employee  performance : and (3) Knowing and analyzing the influence of motivation and work discipline on employee  performance at the Tidore Island City Environmental Agency. The total Sample of the study was 47 people at the Tidore Island City Environmental Agency. The test tool used is multiple linear regression analysis using statistical package for social scientists (SPSS) as a statistical  test tool. The result showed that : (1) Motivation had a positive and significant effect partially on employee performance. This show that motivation is is able to improve the performance of Tidore Island City Environmental Agency Employee : (2) Work discipline has a positive and significant effect partially on employee performance. This show that imployee work discipline is able to improve the performance of employees of the Tidore Island City Environmental Agency: And (3) Motivation (X1) And work discipline (X2) simultaneously have a positive and significant effect on employee performance. This shows that motivation and work discipline are able to improve the performance of employees of the Tidore Island City Environmental Agency.